vrednovanje rezultata merne nesigurnosti izračunatih pomoću dve različite metode i ukupne analitičke greške za ispitivanje etanola - Bozdayi, Mehmet Akif; Bozdayi, Ismet Gamze; Çakırca, Gökhan (Journal of Medical Biochemistry, 2025)
Abstract Background: The analytical performance metrics of ethanol testing are critically important due to their legal implications when presenting and interpreting results. Measurement uncertainty (MU) and total analytical error (TAE) are essential approaches for evaluating and improving the quality of measurement procedures. This study aimed to calculate MU and TAE values, which assess the reliability of ethanol test results from different perspectives, and to evaluate the impact of MU values, calculated using two different methods, on the legal threshold. Methods: MU values were calculated following the guidelines of Nordtest and ISO/TS 20914. TAE was determined using the formula TAE% = 1.65 × CV% + Bias%. External and internal quality control data from ethanol testing conducted between July 1, 2022, and June 30, 2024, were used for calculations. Results: The expanded MU values for ethanol testing were 13.95% according to the Nordtest Guide, 10.94% for low level and 9.59% for high level according to the ISO/TS 20914 Guide. The calculated TAE values were 12.59 for low levels, 11.47 for high levels, and 12.57 overall. MU and TAE values for ethanol testing in our laboratory remained within the allowable total error (±20%) according to CLIA 2024. Conclusions: We believe each laboratory should report ethanol test results and their respective MU values, particularly when evaluating results close to legal thresholds.